An Inquiry on Ancient Natural Theology: The Milesians - Adem İrmak (Milel ve Nihal)

(untitled)
Natural theology is a branch of philosophy that employs empirical and logical methods to gain insight into the nature of God and His attributes. The fundamental structure of natural theology is derived from the tenets of religion and the essential concerns of metaphysics, a branch of philosophy. The arguments for the existence of God represent a central aspect of religious discourse. Consequently, natural theology is situated at the nexus of religion and philosophy. The investigation of the nature of God is a pursuit that has been undertaken since the earliest periods of human history. Nevertheless, within the context of Western philosophy, its roots can be traced back to the ancient Greek tradition. In the last century, there has been a tendency to approach the Pre-Socratics with a certain degree of bias. These philosophers have been viewed in two distinct ways: either as evangelists of the prophetic path or as scientists whose focus was solely on nature and who made no theological claims. This paper examines the possibility of offering an alternative interpretation of their philosophical contributions from the perspective of natural theology. It is proposed that exploring the historical context could provide new insights into studying philosophy and religion. Scholars engaged in the field of the philosophy of religion and those specializing in the history of philosophy may gain new perspectives by tracing the footprints of natural theology within the surviving fragments of the Milesian school